THE EFFECT OF Moringa oliefera LEAF FERMENTED ENRICHED PELLETS ON HEMATOLOGY OF Pangasianodon hypophthalmus REARED IN PHOTOPERIOD SYSTEM - Gusriansyah, Dimas; Syawal, Henni; Riauwaty, Morina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
Moringa leaf (Moringa oleifera) is a herbal plant that has the potential to inhibit bacterial growth and increase immune response. This research was conducted from April to July 2024 at the Biotechnology Laboratory, Faculty of Fisheries and Marine Sciences, Universitas Riau. This study aims to obtain the best dose of fermented moringa leaf added to feed to the immunity of Siamese striped catfish reared on a photoperiod system and tested with A. hydrophila. The research method is the experimental method applying a completely randomized design (CRD) with four treatments and three replicates. Treatment 0 without adding fermented moringa leaves, P1: 10 g/kg feed, P2: 15 g/kg feed, and P3: 20 g/kg feed and challenged with A. hydrophila. The test fish samples measuring 6-7 cm were reared using 100 L buckets of 12 containers with a 30 fish/container stocking density. Feeding was done ad satiation with a frequency of 3 times daily at 08.00, 13.00 and 17.00 WIB. The results showed that adding fermented moringa leaf to the feed affected the immunity of striped catfish. The best dose was found in P1 (10 g/kg feed) with total erythrocytes 2.75 x 106 cells/mm3, hemoglobin level 8.80 g/dL, hematocrit level 34.00%, and total leukocytes 10.86 x 104 cells/mm3, leukocrit level 3.33%, lymphocytes 76.00%, monocytes 7.33%, neutrophils 7.33%, Thrombocytes 9.33%, absolute weight growth 15.02 g/fish, absolute length growth 6.88 cm/fish, 96.67% survival rate. Based on the study's results, feeding added fermented moringa leaves has a significant effect and can improve the immunity of Pangasinodon hypophthalmus